Supporting Pelaksanaan Program Pemeriksaan Kesehatan Berkala Karyawan PT. Pelindo Regional 2 Sunda Kelapa - Sri Sukartono Nathadiharja; Lukiyana Lukiyana; Diansyah Diansyah; Koerniawan Hidajat; Firmansyah Firmansyah; Hanadi Alfadillah (Universitas 17 Agustus 1945 Jakarta, 2026)
Employee health is a crucial element that supports efficiency and the continuity of operations within a company. As one of the strategic state-owned enterprises in the port sector, PT Pelindo has many employees with various levels of occupational risk. Therefore, implementing a periodic health check-up program is an important preventive and promotional measure. The purpose of this community service activity is to raise employees' awareness about the importance of health check-ups, detect potential work-related illnesses early, and motivate the establishment of a healthy work culture. The methods used include regular health examinations, workplace health counseling, and evaluation of the results from these examinations. Findings from this activity indicate an increase in employees' knowledge related to workplace health, as well as the identification of several health risk cases that need to be addressed immediately. With this program, it is expected that employee well-being can improve while simultaneously supporting the company's productivity.